PSMA antibody, humanized PSMA.CAR10.3, or Cetuximab increases prostate cancer localization of NF-κB p50-deficient immature myeloid cells (p50-IMC) and phagocytosis by their macrophage progeny - Mohammad A. Alzubi; Theresa Barberi; Alan D. Friedman (Cancer Immunology, Immunotherapy)
Abstract Adoptive transfer of immature myeloid cells lacking the repressive NF-κB p50 subunit (p50-IMC) slows the growth of syngeneic murine prostate cancer and other tumors. Directing p50-IMC to tumors using Fc receptor-bound antibodies (Abs) or surface chimeric antigen receptors (CARs) may increase tumor localization and subsequent phagocytosis of cancer cells by their mature myeloid progeny, potentiating anti-tumor T cell activation. PSMA and EGFR are found on aggressive human prostate cancers, and p50-IMC express receptors that bind the antibody Fc domain. p50-IMC combined with PSMA Ab, EGFR Ab (Cetuximab), or fully humanized PSMA.CAR10.3 manifest increased localization to Myc-CaP murine prostate cancer tumors expressing PSMA or EGFR. Tumor localization is further increased when myelo-depleting 5-fluorouracil precedes p50-IMC administration. Additionally, we find that PSMA Ab, EGFR Ab, or PSMA.CAR10.3 increase in vitro phagocytosis of Myc-CaP cells expressing PSMA or EGFR by p50-IMC-derived macrophages, including in M2-promoting IL-4, which is a component of the immune-suppressive tumor microenvironment. Lack of tolerance of human PSMA or EGFR by immune-competent mice and lack of expression of human PSMA protein in the prostate of AR2-Probasin-hPSMA transgenic mice precluded our ability to determine whether human-specific PSMA or EGFR antibody or PSMA.CAR10.3 increases anti-tumor efficacy of murine p50-IMC. Nevertheless, this study indicates the potential clinical utility of adding a tumor-directing antibody or CAR, including the novel, fully humanized PSMA.CAR10.3, to proinflammatory p50-IMC to optimize the activation of anti-tumor immunity in prostate cancer and other malignancies, and understanding PSMA toxicity in normal but not malignant prostate epithelium may reveal a novel therapeutic opportunity.